Feeling of loneliness and social new damages in high school students - Nastaran Norouzi Parashkouh; Leila Mirhadyan; Abdolhosein Emami Sigaroudi; Ehsan KazemnejadLeili; Fatemeh Hasandoost (Journal of Holistic Nursing and Midwifery)
Introduction: Loneliness as a predictor of children and adolescents adjustment problems has been focused on by mental health researchers. Increasing virtual relationship instead of family and social relationship especially among adolescents has led to loneliness and other problems.